Injectable platelet-rich fibrin with vitamin C as an adjunct to non-surgical periodontal therapy in the treatment of stage-II periodontitis: a randomized controlled clinical trial - Mohamed Abdulhakim Sherif; Enas Anter; Christian Graetz; Karim Fawzy El-Sayed (BMC Oral Health)
Abstract Background Injectable platelet-rich fibrin (I-PRF) is an autologous fibrin matrix rich in leucocytes, platelets and growth factors, and could serve as a sustained-release vehicle for a variety of active biomolecules. The aim of the current randomized controlled trial was to compare the effect of vitamin C (VitC) with I-PRF as a locally delivered adjunct to professional mechanical plaque removal (PMPR) versus PMPR with local delivery of I-PRF or PMPR alone on non-surgical periodontal treatment (NSPT) outcomes of stage-II periodontitis. Methodology Forty-five patients (n = 45) diagnosed with stage-II grade A periodontitis were randomly assigned into test (PMPR + I-PRF/VitC; n = 15) or control groups (PMPR + I-PRF; n = 15 and PMPR; n = 15). Bleeding on probing (BOP; primary outcome), probing depth (PD), clinical attachment level (CAL), gingival margin (GM), plaque index (PI) and radiographic bone gain/loss (horizontal, vertical and total) were assessed at baseline, three- and six-months post-treatment. Post-operative pain was further assessed at second- and third-day post-treatment. Results Although BOP scores were lower in the PMPR + I-PRF/VitC group, the regression analysis revealed that gender was the only significant predictor for BOP, with females showing a reduced propensity (p < 0.05). Clinical and radiographic parameters significantly improved in all groups independently (p < 0.05). PD-reduction was 1.73 ± 0.59 mm, 1.67 ± 0.49 mm and 1.73 ± 0.59 mm, CAL-change was 1.33 ± 0.49 mm, 1.20 ± 0.56 mm and 0.93 ± 0.59 mm and GM-change was 0.40 ± 0.51 mm, 0.33 ± 0.49 mm and 0.73 ± 0.70 mm in the PMPR + I-PRF/VitC, PMPR + I-PRF and PMPR groups respectively. No intergroup differences were notable regarding BOP or changes in PD, CAL, GM, PI and radiographic bone measurements at three or six months relative to baseline (p > 0.05). Significantly lower pain scores at two and three days were notable in the PMPR + I-PRF/VitC and PMPR + I-PRF groups compared to the PMPR group (p < 0.05). Conclusions Apart from a positive effect on the patients’ post operative pain perception, I-PRF with or without the addition of vitamin C does not additionally improve the clinical outcomes of PMPR alone in the NSPT of stage-II grade A periodontitis patients. Trial registration Trial registration. The study was retrospectively registered in the US National Institutes of Health Clinical Trials Registry (NCT05129267) on 2021-11-10.